Destabilized identities and the question of London in Abdulrazak Gurnah's by the sea - Al-Badarneh, Abdullah F.; Wassel, Carly J. (Penerbit Universiti Kebangsaan Malaysia, 2024)
This article analyzes the intricacies and possibilities of home to refugees in Abdulrazak Gurnah’s novel By the Sea (2001). It explores the role of the city—London—in the novel in (de)stabilizing diasporic identities, providing a counter-discursive argument against John Clement Ball’s claim that the city can empower migrants. The two protagonists of the novel, Saleh Omar and Latif Mahmud, migrate from Zanzibar, once a protectorate of the British empire in the East African Indian Ocean, to England. They never romanticize their imagined home, Zanzibar, recalled in memory, or cherish their adopted home, England. Gurnah offers a view of the postcolonial experience in the metropolis of London and makes it much more open to interpretation. He reverses the potential the city can offer to refugees and migrants. Gurnah demonstrates that London fails to offer a home, in the full sense of the word, for the protagonists in By the Sea. Through shedding light on Omar’s and Latif’s restless identities in the host country, particularly in London, their past bitter memories, and the resulting sentiments of fear and instability, this study concludes that diasporic identities never fulfill a complete sense of contentment in the host country. Contrary to Ball’s belief, the study further asserts that London—as an adopted city home—provides a space for refugees’ self-fulfillment, but this space is devoid of their peace of mind and attachment. London, then, does not transcend from space to place or from place to home.